Diet and habit explain head‐shape convergences in natricine snakes. (13th December 2022) - Deepak, V.; Gower, David J.; Cooper, Natalie
Abstract: The concept of ecomorphs, whereby species with similar ecologies have similar phenotypes regardless of their phylogenetic relatedness, is often central to discussions regarding the relationship between ecology and phenotype. However, some aspects of the concept have been questioned, and sometimes species have been grouped as ecomorphs based on phenotypic similarity without demonstrating ecological similarity. Within snakes, similar head shapes have convergently evolved in species living in comparable environments and/or with similar diets. Therefore, ecomorphs could exist in some snake lineages, but this assertion has rarely been tested for a wide‐ranging group within a single framework. Natricine snakes (Natricinae) are ecomorphologically diverse and currently distributed in Asia, Africa, Europe and north‐central America. They are primarily semiaquatic or ground‐dwelling terrestrial snakes, but some are aquatic, burrowing or aquatic and burrowing in habit and may be generalist or specialist in diet. Thus, natricines present an interesting system to test whether snakes from different major habit categories represent ecomorphs. We quantify morphological similarity and disparity in head shape among 191 of the ca. 250 currently recognized natricine species and apply phylogenetic comparative methods to test for convergence. Natricine head shape is largely correlated with habit, but in some burrowers is better explained by dietary specialism. Convergence in head shape is especially strong for aquatic burrowing, semiaquatic and terrestrial ecomorphs and less strong for aquatic and burrowing ecomorphs. The ecomorph concept is useful for understanding natricine diversity and evolution, though would benefit from further refinement, especially for aquatic and burrowing taxa. Abstract : We studied head shape variation in natricine snakes with respect to ecology. Using a phylogenetic framework, we test the hypotheses that natricine head shape variation is explained by variation in habit and diet and evaluate evidence for ecomorphs within the group. We quantified morphological similarity and disparity in head shape among 191 of the ca. 250 currently recognized natricine species and applied phylogenetic comparative methods to test for convergence. Natricine head shape is largely correlated with habit but in some burrowers is better explained by dietary specialism. Convergence in head shape is especially strong for aquatic burrowing, semiaquatic and terrestrial ecomorphs and less strong for aquatic and burrowing ecomorphs.